Behavioural Treatments for Tourette Syndrome: An Evidence-Based Review - Madeleine Frank; Andrea Eugenio Cavanna (Behavioural Neurology)
Tourette syndrome (TS) is a disorder characterised by multiple motor and vocal tics and is frequently associated with behavioural problems. Tics are known to be affected by internal factors such as inner tension and external factors such as the surrounding environment. A number of behavioural treatments have been suggested to treat the symptoms of TS, in addition to pharmacotherapy and surgery for the most severe cases. This review compiled all the studies investigating behavioural therapies for TS, briefly describing each technique and assessing the evidence in order to determine which of these appear to be effective. Different behavioural therapies that were used included habit reversal training (HRT), massed negative practice, supportive psychotherapy, exposure with response prevention, self-monitoring, cognitive-behavioural therapy, relaxation therapy, assertiveness training, contingency management, a tension-reduction technique and biofeedback training. Overall, HRT is the best-studied and most widely-used technique and there is sufficient experimental evidence to suggest that it is an effective treatment. Most of the other treatments, however, require further investigation to evaluate their efficacy. Specifically, evidence suggests that exposure with response prevention and self-monitoring are effective, and more research is needed to determine the therapeutic value of the other treatments. As most of the studies investigating behavioural treatments for TS are small-sample or single-case studies, larger randomised controlled trials are advocated.